Peningkatan Kesadaran Masyarakat terhadap Risiko Konsumsi Pemanis Buatan - Rallyanta Tarigan; Amalia Malik; Rini Hardiyani; Helda Jaya Puspita; Nova Hidayati Diyah Larasati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Artificial sweeteners are widely present in food and beverages consumed in daily life. However, many consumers remain unaware of the potential negative impacts of artificial sweetener consumption. This study aims to evaluate the public's understanding of the adverse effects associated with artificial sweeteners. The method used involves active participation through direct education, incorporating pre-test and post-test questionnaires. The pre-test results show that 6 respondents, accounting for 37% of the total 20 respondents, were unaware of the long-term negative impacts. In contrast, the post-test results indicate that all respondents agreed to reduce their consumption of artificial sweeteners to mitigate potential adverse effects.